2005
DOI: 10.1111/j.1439-0396.2005.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and metabolism of zearalenone in young female pigs

Abstract: The fate of a single bolus of the Fusarium mycotoxin zearalenone (ZON) given intravenously to pigs was followed up. Pigs were equipped with duodenal re-entrant cannulas, post-valvular T-shape cannulas and with a urinary bladder balloon catheter. The animals were divided into three groups. Pigs of the control group were injected with ZON (Co), and pigs of the second group were also injected with ZON but their duodenal digesta was quantitatively exchanged for 12 h with corresponding pigs of the third group, not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
5
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 13 publications
8
62
5
1
Order By: Relevance
“…7). The latter undergoes an intensive enterohepatic cycling [29,30] and its metabolites accumulate in the bile. Bile concentrations of these metabolites were shown to be linearly related to the ZON concentration of piglet diets [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). The latter undergoes an intensive enterohepatic cycling [29,30] and its metabolites accumulate in the bile. Bile concentrations of these metabolites were shown to be linearly related to the ZON concentration of piglet diets [31].…”
Section: Discussionmentioning
confidence: 99%
“…Bile concentrations of these metabolites were shown to be linearly related to the ZON concentration of piglet diets [31]. Moreover, the concentration of ZON metabolites in bile was approximately twofold to eightfold higher than the respective concentrations in urine although the majority of ZON metabolites is excreted quantitatively via urine [29,30]. That no ZON residues were detected in serum of the gilts is consistent with the findings of Döll et al [31] who were not able to detect ZON metabolites in serum of piglet fed diets up to a ZON concentration of 420 lg N kg -1…”
Section: Discussionmentioning
confidence: 99%
“…In a dose-response study conducted by Döll et al (2003), ZEA and αZOL in pooled urine samples were found to vary with increased levels of ZEA in the diet. Also, in the study of Dänicke et al (2005a) with graded fusariumtoxins to pigs, a significant linear increase in ZEA and αZOL concentrations in bile and urine were found due to increased dietary ZEA levels.…”
Section: Introductionmentioning
confidence: 92%
“…Similar results have also been found in more recent studies (Eriksen et al 2003;Dänicke et al 2004a,b) when analyzing pig urine for DON and DeepoxyDON after DON or 3acetylDON consumption. About 40-60% of DON in urine is glucuronide conjugated (Eriksen et al 2003;Dänicke et al 2005a). The amount of DeepoxyDON in urine is normally only about 2-5% of the DON in urine, and 1-5% of the DON intake (Dänicke et al 2004a, b, c;.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have showed that pathologic changes appeared in pigs exposed to 0.42~1.3 mg ZEN/kg diet (Döll et al, 2004;Teixeira et al, 2011;Jiang et al, 2010a). Zearalenone is metabolized in various tissues, with the major metabolites being α-zearalenol and β-zearalenol (Dänicke et al, 2005;Malekinejad et al, 2005).…”
Section: Introductionmentioning
confidence: 99%